Information requirements to create public value: sharing and opening data to address urban blight. Issue 1 (20th March 2017) - De Tuya, Manuel; Cook, Meghan; Sutherland, Megan K.; Luna-Reyes, Luis Felipe
Abstract : Purpose: Blighted and vacant properties represent a persistent and costly problem for cities and local governments throughout the USA. The purpose of this paper is to identify data needs and requirements for value creation in the context of urban blight. The main assumption is that sharing and opening data through a robust and effective code enforcement program will facilitate more informed management, mitigation and remediation of blighted and vacant properties. Code enforcement programs must be grounded on organizational and technical infrastructures that enable data sharing and value creation for the city and the communities that share its space. Design/methodology/approach: In this paper, the information needs and realities of a city's code enforcement environment are described, based on data gathered through a series of workshops and focus groups with a range of stakeholders, which included city government departments, police, fire, bank representatives, realtors and community groups. Findings: The analysis reveals key data elements that could potentially help to build a code enforcement program to better manage the cycles and costs of urban blight. Although some of these data elements already exist, and are public, they are not easily accessible to key stakeholders. The paper ends with sets of short-term and long-term recommendations for establishing an information-sharing infrastructure, which would serve as the main conduit for exchanging code enforcement data among a number of city government departments and the public that may play a role in managing urban blight and its consequences. Originality/value: In this paper, the authors are connecting extant literature on sharing and opening data with literature on the creation of public value. They argue that sharing and opening government data constitute effective ways of managing the costs and cycles of urban blight while creating value. As a result of an initial assessment of data and information requirements, the authors also point to specific data and its potential value from stakeholder perspective.